Assessment of Different Techniques to Detect Recurrent Carious Lesion Around Amalgam Filling - Noor M. Kadhim; Ban A. Salih (College of Dentistry/ University of Baghdad, 2017)
Abstract Background: This in-vitro study was to evaluated bitewing radiograph and tactile examination for detection secondary caries adjacent to amalgam restorations. Material and method: Sixty primary extracted molars with class I and class II amalgam restorations were selected from children, and examined by bitewing radiographs were taken by using film holders and interpreted on a backlit screen without magnification. Then, we used tactile examination with blunt probe. Result: The result of this study showed that the best cut-off points for the sample were found by a Receiver Operator Characteristic (ROC) analysis, and the area under the ROC curve and the sensitivity, specificity and accuracy of the techniques were calculated for enamel (D1) and dentine (D2) thresholds. These parameters were found for each techniques and then compared by the Cochran's Q test. The tactile examination presented the fair techniques for detecting secondary caries at enamel thresholds for both occlusal and proximal surfaces, While, bitewing radiograph presented good techniques at dentin thresholds. Conclusion: Tactile examination represented the best performance for detecting enamel secondary caries. While, bitewing radiograph represented the best performance for detecting dentin secondary caries